Al Ikhtiyaajaat wa ad-Dawaafi’ Li asy-Syakhsiyyah ar-Roiisiyyah fi al-Qisshotaini al-Qoshiirotaini “Ash’udu Zaujaini” wa “Ana al-Maut” Li Taufiq al-Hakim (‘Ilmu an-Nafsi al-Adabi Li Henry Murray) - Raenza Agung Pratama (Journal of Arabic Literature (JaLi), 2022)
The short story entitled "The Happiest Couple" is set about a man who wants to marry his beloved woman, whom the man knows through radio broadcasts on a cooking channel, and about the man's life after marrying the woman. The short story "I am The Death" is about the ambition of a rich and intelligent man who wants to move to another world by committing suicide, but is prevented by a woman and ends up changing his mind. In the end, the two short stories provide dialogue between characters and explain the character's behavior. These two short stories are included in a collection of stories entitled "Arinillah" by the famous writer Taufiq Al-Hakim. The aims of this study are as follows: (1) To find out the shape of the needs and motives of the main character in the short stories " The Happiest Couple" and "I am The Death" by Taufiq Al-Hakim. (2) To find out the description of the main character in the short stories "The Happiest Couple" and "I am The Death" by Taufiq Al-Hakim. This study uses the theory of personality psychology from Henry Murray's perspective.This research is a descriptive and qualitative research. This study used several data collection techniques such as reading and note-taking techniques. From the results of the research and discussion conducted, it can be seen that each main character has the same type of needs, but each main character has his own way or action to fulfill his needs. Behavior can be influenced and affect the environment and the people around him. Besides, we can't have everything we need according to what we want. However, the person will continue to try to fulfill his needs.